2012
DOI: 10.1073/pnas.1119460109
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of the metal-binding region in apo-cupredoxins

Abstract: Protein-mediated electron transfer is an essential event in many biochemical processes. Efficient electron transfer requires the reorganization energy of the redox event to be minimized, which is ensured by the presence of rigid donor and acceptor sites. Electron transfer copper sites are present in the ubiquitous cupredoxin fold, able to bind one or two copper ions. The low reorganization energy in these metal centers has been accounted for by assuming that the protein scaffold creates an entatic/rack-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 66 publications
8
70
0
1
Order By: Relevance
“…2B). This selectivity confirms that these loops are indeed crucial for recognition in the copper transfer event (33). On the other hand, Cu(I)-Sco2 shows impaired metal transfer ability but is able to reduce the cysteines of apo-COX II* S-S at a 2:1 stoichiometry.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…2B). This selectivity confirms that these loops are indeed crucial for recognition in the copper transfer event (33). On the other hand, Cu(I)-Sco2 shows impaired metal transfer ability but is able to reduce the cysteines of apo-COX II* S-S at a 2:1 stoichiometry.…”
Section: Discussionsupporting
confidence: 56%
“…The heteronuclear single-quantum correlation (HSQC) spectra of 15 N apo-COX II* 2SH (where 2SH indicates that the Cys ligands are in the reduced state) show upon copper(I) titration (i) chemical shift perturbations of resonances corresponding to residues close to the metal-binding region, and (ii) the appearance of several cross peaks corresponding to residues in the engineered loops (Fig. S2) that were not observed in the spectrum of the metal-free protein, most likely broadened because of conformational exchange processes occurring in the intermediate regime (33). These differences in the NMR spectra of apo and di-Cu(I) forms of COX II* can be exploited to follow copper uptake from the potential protein donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This rule, first reported in 1938, was based on analyses of electrical transport measurements of oxide semiconductors,28 where it was observed that the activation energy ( E a ) of the conduction is proportional to the temperature‐independent preexponential factor. This means that if the conduction is thermally activated: I=I0exp(Enormala/knormalBT), the prefactor I0exp(Enormala/knormalBTMN), where T MN is the Meyer–Neldel temperature 29.…”
Section: Resultsmentioning
confidence: 97%